Impact of air pollution to genome of newborns - Šrám, Radim J; Rössner, Pavel; Rössnerová, Andrea; Dostál, Miroslav; Milcová, Alena; Švecová, Vlasta; Pulkrabová, Jana; Hajšlová, Jana; Velemínský, Miloš (Central European Journal of Public Health, 2016)
The Northern Moravia Region is the most polluted region in the Czech Republic by particulate matter (PM2.5) and carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) as benzo[a]pyrene (B[a]P) by heavy industry and local heating. This specific situation was used to study the impact of air pollution on newborns in the exposed Karviná district and control district of České Budějovice. Biological material from newborns and mothers was collected in summer and winter seasons. This project is highly detailed, analyzing the concentrations of PAHs in ambient air and diet, in human breast milk, in the urine of mothers and newborns, using biomarkers of genetic damage as DNA adducts and gene expression analysis, biomarkers of oxidative stress as 8-oxodG adducts and lipid peroxidation (15-F2t-isoprostane immunoassay). All 400 children, for whom the biomarker data at delivery were obtained, will be followed for morbidity up to 2 years of age. The Northern Moravia Region seems to be to be a model area for studying the long-term impact of human health exposure to c-PAHs. Our observations will indicate possible genetic and oxidative damage in newborns, which may significantly affect their morbidity.
Keywords: polycyklické aromatické uhlovodíky; Oxidative Stress; novorozenec; Infant, Newborn; oxidační stres; pevné částice; Humans; Pregnancy; Deoxyguanosine; Diet; Environmental Monitoring; průmysl; mateřské mléko; Female; vystavení vlivu životního prostředí; dospělí; genom; Industry; Genome; lidé; Polycyclic Aromatic Hydrocarbons; Air Pollutants; Particulate Matter; látky znečišťující vzduch; Adult; monitorování životního prostředí; roční období; ženské pohlaví; Milk, Human; Male; deoxyguanosin; dieta; Benzo(a)pyrene; Seasons; těhotenství; Czech Republic; Real-Time Polymerase Chain Reaction; Environmental Exposure; Česká republika; mužské pohlaví; benzopyren; adukty DNA; DNA Adducts; kvantitativní polymerázová řetězová reakce